Effects of high pressure and thermal processing on quality properties and volatile compounds of pineapple fruit juice. (December 2021) - Wu, Wanlin; Xiao, Gengsheng; Yu, Yuanshan; Xu, Yujuan; Wu, Jijun; Peng, Jian; Li, Lu
Abstract: Traditional pasteurization method usually has negative impacts on color, flavor, and bioactive compounds of fresh fruit juice. Therefore, it is critically important to develop novel non-thermal sterilization technologies to overcome these problems. In this study, high pressure processing (HPP) (500 MPa/10 min) and thermal processing (TP) (95 °C/3 min) treatments on pineapple fruit juice were comparatively evaluated by monitoring their influences on microbial counts, physicochemical parameters, bioactive components, antioxidant capacity, and volatile compounds during storage of 28 days at 4 °C. The microbial safety was ensured in both HPP-treated and TP-treated pineapple fruit juice, and further cold storage result showed at least a shelf life of 21 days at 4 °C. Both HPP and TP treatments have significant effects on the turbidity and sedimentation index of pineapple juice. During the shelf life, the sugars, pH, titratable acidity, total soluble solids, and sedimentation index of HPP-treated groups exhibited no significant change, while the color, bioactive components, antioxidant capacity, and relative content of volatile compounds in both TP- and HPP-treated groups were remarkably changed. Moreover, the pineapple fruit juice with HPP treatment showed a greater retention of original color, bioactive components, antioxidant activity, and volatile compounds in comparison with TP-treated group. In summary, HPP treatment could not only control the microbes in pineapple fruit juice, but also better retain the qualities of pineapple fruit juice, which provided an effective alternative to conventional thermal processing for production of high quality pineapple fruit juice. Highlights: HPP treatment had no significant influence on physicochemical properties of pineapple fruit juice. HPP-treated pineapple fruit juice retained higher levels of bioactive ingredients and antioxidant capacity. The aroma composition of HPP-treated pineapple fruit juice was closer to fresh pineapple fruit juice.